2014
DOI: 10.4049/jimmunol.1400019
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Control of Mycobacterium tuberculosis Infection by a Subset of Lung Parenchyma–Homing CD4 T Cells

Abstract: Th1 cells are critical for containment of Mycobacterium tuberculosis infection, but little else is known about the properties of protective CD4 T cell responses. In this study, we show that the pulmonary Th1 response against M. tuberculosis is composed of two populations that are either CXCR3hi and localize to lung parenchyma or are CX3CR1hiKLRG1hi and are retained within lung blood vasculature. M. tuberculosis–specific parenchymal CD4 T cells migrate rapidly back into the lung parenchyma upon adoptive transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
396
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(420 citation statements)
references
References 19 publications
19
396
3
2
Order By: Relevance
“…In addition, we observed only minimal expression of CXCR3 and CCR5, on both CD103 + and CD103 2 IFN-g + CD8 + T cell subsets. These findings differ from recent observations in M. tuberculosis-infected mice, which show high expression of CXCR3 on lung T RM cells (16). More study of chemokine receptors on influenza-specific lung T RM cells is required to elucidate to importance of chemokine receptors in establishing tissue residence.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In addition, we observed only minimal expression of CXCR3 and CCR5, on both CD103 + and CD103 2 IFN-g + CD8 + T cell subsets. These findings differ from recent observations in M. tuberculosis-infected mice, which show high expression of CXCR3 on lung T RM cells (16). More study of chemokine receptors on influenza-specific lung T RM cells is required to elucidate to importance of chemokine receptors in establishing tissue residence.…”
Section: Discussioncontrasting
confidence: 56%
“…5E). As PD-1, a cell surface marker of activated T cells is known to express on T RM cells (16,35), we showed that high expression of PD-1 was consistently detected on lung CD103 + compared with CD103 2 IFN-g + CD8 + T cells. In addition, the expression levels of chemokine receptors involved in T cell migration into the lung (36, 37), CXCR3 and CCR5, were minimal with no significant difference between either subset (Fig.…”
Section: Rhesus Lung Np-specific Memory T Cells Expressed Phenotypic mentioning
confidence: 74%
See 2 more Smart Citations
“…The availability of the recently developed technique of intravascular staining helps to discriminate pulmonary intravascular and lung tissue T-cell populations for the first time [16,17], and appreciate their relationship with anti-TB protection. In our previous studies we have reported that, regardless of route of immunisation, a large population of anti-TB T-cells can be isolated from perfused mouse lungs [12,13].…”
Section: Protection Against Pulmonary Tb Is Determined By the Differementioning
confidence: 99%